2006
DOI: 10.1080/10428190500404761
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant chronic lymphocytic leukemia and acute myeloid leukemia: Evidence of simultaneous expansion of two independent clones

Abstract: The simultaneous appearance of chronic lymphocytic leukemia (CLL) and acute myeloid leukemia (AML) has been rarely reported, with AML occurring more frequently as a secondary event in patients receiving cytotoxic drugs for a primary lymphoproliferative disorder. We describe a case of simultaneous CLL and AML documented by morphological and cytometric analysis in a previously untreated patient. In particular, on the basis of morphological and immunological features, the patient was diagnosed as being affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
1
13
0
3
Order By: Relevance
“…By contrast, IGH alterations were not present in any of the CD34+ hematopoietic progenitors. Previous case report studies have yielded similar results [34, 35], suggesting that IGH alterations occur in an advanced stage of the lymphocyte maturation process.…”
Section: Discussionsupporting
confidence: 72%
“…By contrast, IGH alterations were not present in any of the CD34+ hematopoietic progenitors. Previous case report studies have yielded similar results [34, 35], suggesting that IGH alterations occur in an advanced stage of the lymphocyte maturation process.…”
Section: Discussionsupporting
confidence: 72%
“…Regarding primary etiology, impaired immunity and old age have been discussed previously [6]; our patient had both these risk factors. Graf [7] suggested that, due to the plasticity of neoplastic common progenitor cells, the neoplastic transformation of common progenitor cells could occur during hematopoietic differentiation, and they could develop into two separate lineages (myeloid and lymphoid).…”
mentioning
confidence: 54%
“…13,14 However, most types of non-Hodgkin lymphoma that have previously been associated with a diagnosis of MDS were slowly progressive forms of chronic lymphocytic leukemia (Cll), in which the development of MDS (and in some instances even AMl) followed chemotherapy with leukemo genic alkylating agents-and might, thus, have been therapyrelated 7 -or a long period of presumed immunosuppression from disease-related lymphocytopenia. 14,15 Much debate has taken place concerning the nature of this concomitant occurrence of MDS and Cll and, although the involvement of common leukemo genic or stem-cell mechanisms could not always be excluded, several cases have been demonstrated to result from neoplastic clones within different cell lineages. 14,15 In the patient discussed here, MDS-or at least an uncommonly long preceding 4-year period of macrocytic anemia and, eventually, pancytopenia-marked a disease process that eventually culminated in a rapidly progressive syndrome of Ivl.…”
Section: Discussion Of Diagnosismentioning
confidence: 99%
“…14,15 Much debate has taken place concerning the nature of this concomitant occurrence of MDS and Cll and, although the involvement of common leukemo genic or stem-cell mechanisms could not always be excluded, several cases have been demonstrated to result from neoplastic clones within different cell lineages. 14,15 In the patient discussed here, MDS-or at least an uncommonly long preceding 4-year period of macrocytic anemia and, eventually, pancytopenia-marked a disease process that eventually culminated in a rapidly progressive syndrome of Ivl. Despite a relative paucity of literature on this topic, several other cases have been reported in which Ivl followed a previous diagnosis of MDS.…”
Section: Discussion Of Diagnosismentioning
confidence: 99%